CULTIVATING STUDENT ENGAGEMENT IN CHRISTIAN RELIGIOUS EDUCATION: A QUALITATIVE LITERATURE REVIEW - Edwin Melky Lumingkewas; Juwinner Dedy Kasingku (CV. TOTUS TUUS, 2026)
Christian Religious Education (CRE) is pivotal for whole-person formation, yet classroom practice often remains teacher-centered, suppressing student participation. This study aimed to identify effective instructional approaches that foster active engagement in CRE lessons. Using a qualitative library research design, we thematically reviewed books, peer-reviewed articles, and relevant reports on student participation and pedagogies applicable to CRE. Findings indicate two consistently effective approaches: cooperative learning (e.g., Think–Pair–Share, Jigsaw, Team Games Tournament, and “window shopping”) and problem-based learning. These models elevate engagement across cognitive (analysis, evaluation, problem solving), affective (interest, motivation, positive attitudes), and psychomotor (practice and performance) domains. The CRE teacher’s role as facilitator and spiritual mentor—backed by professional competence in content mastery, classroom management, creativity, and communication—proves crucial for creating interactive, joyful, and meaningful learning climates. We conclude that participatory models enable students to not only grasp doctrine cognitively but also embody Christian values in daily life. The results offer practical guidance for CRE teachers, curriculum developers, and teacher-training programs to design student-centered learning. Future studies should test these approaches using quasi-experimental, mixed-methods, and longitudinal designs to assess impacts on character formation, faith development, and transferability across grades and school contexts.